A new species of Stelis (Pleurothallidinae, Orchidaceae) from South Yungas, Bolivia - Steudel, Bastian (Phytotaxa, 2011)
A new species of Stelis from Bolivia is described and illustrated. Stelis stephanii is only known from the type collection.